2008
DOI: 10.1103/physrevb.77.134409
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostatic interactions on a square lattice

Abstract: The metastable zero field magnetic states of elongated Permalloy islands on square lattices of different geometries are investigated by means of magnetic force microscopy and numerical calculations. Keeping the island shape L / w = 10 fixed while varying the interparticle distances a, it is demonstrated that the relative frequencies of observed magnetic configuration at remanence strongly depend on the packing density of an array and the magnetic history ͑i.e., in which direction the array has been saturated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 9 publications
3
81
0
2
Order By: Relevance
“…As experimentally shown in Ref. [8], this metastable state is a very real possibility when magnetic fields are applied. In this case only the topology of type (b) of Fig.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…As experimentally shown in Ref. [8], this metastable state is a very real possibility when magnetic fields are applied. In this case only the topology of type (b) of Fig.…”
Section: Discussionmentioning
confidence: 87%
“…[8,9]. We would like to remark that although this is the ground state, its thermal equilibration in experiments seems to be very difficult [8,9,10]. Once the system is naturally frustrated, in the two-in/two-out configuration, the effective magnetic charge Q i,j M (number of spins pointing inward minus the number of spins pointing outward on each vertex (i, j)) is zero everywhere.…”
Section: The Model and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A wide range of interesting behavior 2,3 can be observed in these artificial frustrated magnets by tuning the geometry of square [4][5][6][7] , triangular 8,9 , hexagonal (and kagome) [10][11][12][13][14][15][16][17][18][19][20] and brickwork lattices, as well as isolated clusters 21 . In particular, the local moment behavior of these systems has shown that they are good realizations of ice models, and a range of studies have examined monopole excitations and drawn upon close analogies with the pyrochlore spin ice materials.…”
Section: Figmentioning
confidence: 99%